History of traumatic brain injury interferes with accurate diagnosis of Alzheimer's dementia: a nation-wide case-control study. (2nd January 2020) - Pradeep, Tejus; Bray, Michael J. C.; Arun, Siddharth; Richey, Lisa N.; Jahed, Sahar; Bryant, Barry R.; LoBue, Christian; Lyketsos, Constantine G.; Kim, Paul; Peters, Matthew E.
Abstract: Traumatic brain injury (TBI) and Alzheimer's disease (AD) bear a complex relationship, potentially increasing risk of one another reciprocally. However, recent evidence suggests post-TBI dementia exists as a distinct neurodegenerative syndrome, confounding AD diagnostic accuracy in clinical settings. This investigation sought to evaluate TBI's impact on the accuracy of clinician-diagnosed AD using gold standard neuropathological criteria. In this preliminary analysis, data were acquired from the National Alzheimer's Coordinating Centre (NACC), which aggregates clinical and neuropathologic information from Alzheimer's disease centres across the United States. Modified National Institute on Aging-Reagan criteria were applied to confirm AD by neuropathology. Among participants with clinician-diagnosed AD, TBI history was associated with misdiagnosis (false positives) (OR = 1.351 [95% CI: 1.091–1.674], p  = 0.006). Among participants without clinician-diagnosed AD, TBI history was not associated with false negatives. TBI moderates AD diagnostic accuracy. Possible AD misdiagnosis can mislead patients, influence treatment decisions, and confound research study designs. Further work examining the influence of TBI on dementia diagnosis is warranted.